2013
DOI: 10.2337/db12-1179
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Onset of Oral Lipid–Induced Skeletal Muscle Insulin Resistance in Humans

Abstract: Several mechanisms, such as innate immune responses via Toll-like receptor-4, accumulation of diacylglycerols (DAG)/ceramides, and activation of protein kinase C (PKC), are considered to underlie skeletal muscle insulin resistance. In this study, we examined initial events occurring during the onset of insulin resistance upon oral high-fat loading compared with lipid and low-dose endotoxin infusion. Sixteen lean insulin-sensitive volunteers received intravenous fat (iv fat), oral fat (po fat), intravenous endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 98 publications
(128 citation statements)
references
References 51 publications
12
115
1
Order By: Relevance
“…Although it is possible that the low content of saturated FAs in the lipid infusion used in the current study might explain this discrepancy, a recent study found that saturated fat-induced insulin resistance can occur independently of TLR4 activation and increased in tissue ceramide content (35). Finally, markers of systemic inflammation, IL-6, adiponectin, RBP4, and sICAM-1, which have all been implicated in causing insulin resistance in obese and T2D (14) individuals, remained unchanged during the lipid infusion, thus dissociating these factors from lipid-induced muscle insulin resistance in this study (24).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although it is possible that the low content of saturated FAs in the lipid infusion used in the current study might explain this discrepancy, a recent study found that saturated fat-induced insulin resistance can occur independently of TLR4 activation and increased in tissue ceramide content (35). Finally, markers of systemic inflammation, IL-6, adiponectin, RBP4, and sICAM-1, which have all been implicated in causing insulin resistance in obese and T2D (14) individuals, remained unchanged during the lipid infusion, thus dissociating these factors from lipid-induced muscle insulin resistance in this study (24).…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies in rodent models have implicated increases in myocellular lipid metabolites, such as ceramides and DAGs, with subsequent inhibition of insulin signaling as causal factors in the pathogenesis of lipid-induced muscle insulin resistance (5,6,10,11,23). Studies in humans have been less conclusive because of conflicting results of studies with different experimental protocols, resulting in varying plasma FA concentrations and compositions (15,16,24). By performing serial muscle biopsies before and during a lipid infusion, we found that total muscle DAG content increased transiently within 2.5 h and subsequently declined 4 h after starting the lipid infusion.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…VO 2 and VCO 2 were measured, and substrate oxidation rates were calculated as previously described (23). Nonoxidative glucose disposal was calculated as the difference between R d and oxidative glucose utilization.…”
Section: Indirect Calorimetrymentioning
confidence: 99%
“…Studies using parenteral administration of unsaturated lipids (18) or high-calorie mixed meals yielded conflicting results with regard to hepatic energy metabolism. One mixed-meal study found greater de novo lipogenesis without affecting hepatic glycogen metabolism (12), while an intravenous lipid infusion study failed to detect any effect on hepatic insulin sensitivity (19). Another study com-BACKGROUND.…”
Section: Introductionmentioning
confidence: 99%